A Comparative study of knowledge and perceived skills regarding emergency care during disaster between community health volunteers working in Tsunami-Affected and Non-Affected areas in Aceh Province, Indonesia - Anda Kamal (Prince of Songkla University, 2013)
Thesis (M.N.S., Nursing Sciences)--Prince of Songkla University, 2012